Leadership strategy and tactics : field manual - Willink, Jocko (London : Macmillan, 2020)
THE INSTANT #1 INTERNATIONAL BESTSELLER Leadership Strategy and Tactics: Field Manual by Jocko Willink is the essential and practical guide to leadership and how to excel at it, from the co-author of the number one New York Times bestseller Extreme Ownership. Leadership is the most challenging of human endeavours. It is often misunderstood. It can bewilder, mystify and frustrate even the most dedicated practitioners. Leaders at all levels are often forced to use theoretical guesswork to make decisions and lead their troops. It doesn't have to be that way. There are principles that can be applied and tenets that can be followed. There are skills that can be learned and manoeuvres that can be practised and executed. There are leadership strategies and tactics that have been tested and proven on the battlefield, in business and in life. Retired Navy SEAL Officer Jocko Willink delivers his powerful and pragmatic leadership methodology that teaches how to lead any team in any situation to victory. Here, you will learn how to: *Deal with egos and the problems they cause *Earn and build trust with both your subordinates and superiors *Instil pride in your team, without creating arrogance *Overcome challenges presented by a micromanaging, indecisive or weak boss *Create a disciplined team that regulates itself *Use leadership as a tool to teach, mentor, train and correct behaviour of team members *Operate at a maximum level of efficiency - and reap the rewards . . . and more. This book is step one towards becoming the commander of your own life. The rest is up to you.
Reprint. Originally published: New York, NY : St. Martin's Press, 2020.
Includes index.
Keywords: Leadership; Strategic planning